View of the master bedroom in Mr. and Mrs. Monte Drake's home - Drake, Elaine Perpetua (1978)
Photo faisant partie d'une série associée à une dissertation trimestrielle d'étudiant(e) en folklore à l'université Memorial: « A Description of the Interior of the Home of Mr. and Mrs. Monte Drake in the Community of Lourdes on the West Coast of Newfoundland, Bay St. George ». -- Photo is one of a series associated with a Memorial University folklore student term paper: "A Description of the Interior of the Home of Mr. and Mrs. Monte Drake in the Community of Lourdes on the West Coast of Newfoundland, Bay St. George".